Метод моторної оцінки захисних властивостей моторних олив двигунів внутрішнього згоряння - Калінін, Євген Іванович; Ребров, Олексій Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У роботі представлено результати розробки та експериментального обґрунтування методу прискореної оцінки захисних (антикорозійних) властивостей моторних олив в умовах, максимально наближених до реальної експлуатації двигунів внутрішнього згоряння. Експериментально встановлено, що при температурах охолоджувальної води та оливи нижче 40 °С на поверхні гільзи циліндра створюються умови для інтенсивної корозії, що супроводжується різким зростанням вмісту водного конденсату в оливі та підвищенням ступеня конденсації картерних газів. Обґрунтовано доцільність використання комбінованого режиму випробувань, який включає «холодний» етап роботи двигуна, зупинку з примусовим прокачуванням охолоджувальної рідини підвищеної температури та подальшу роботу на "гарячому" режимі. Показано, що такий режим забезпечує інтенсифікацію корозійних процесів і водночас дозволяє отримати відтворювані результати за відносно короткий час. Запропоновано критерії оцінки захисних властивостей моторних олив за індукційним періодом корозії, кількістю деталей з корозійними осередками, площею та характером корозійних уражень контрольної пластини та елементів газорозподільного механізму. Встановлено кореляційний зв’язок між величиною зношування гільзи циліндра та показниками корозійного ураження контрольних елементів, що дозволяє застосовувати спрощену експрес-оцінку без тривалих ресурсних випробувань. У результаті оптимізації тривалості циклів визначено раціональний тригодинний режим випробувань, який забезпечує чітку фіксацію початку індукційного періоду корозії та підвищує чутливість методу до відмінностей у захисних властивостях різних олив. Проведені порівняльні випробування показали, що введення комбінованих інгібіторів корозії істотно підвищує антикорозійну ефективність моторних олив, тоді як найвищі захисні властивості демонструють синтетичні робочо-консерваційні оливи з інгібіторами комплексної дії. Запропонований метод може бути використаний для наукових досліджень, розробки та порівняльної оцінки моторних олив за рівнем їх захисних властивостей.

The paper presents the results of the development and experimental substantiation of a method for accelerated assessment of the protective (anti-corrosion) properties of motor oils in conditions as close as possible to the real operation of internal combustion engines. It is shown that the determining condition for the development of electrochemical corrosion of parts of the cylinder-piston group is the presence of an electrolyte film on their surface, the formation of which is due to the condensation of water vapor and crankcase gas components at low-temperature engine operation modes, as well as during its shutdown. It was experimentally established that at temperatures of cooling water and oil below 40 °C, conditions for intensive corrosion are created on the surface of the cylinder liner, which is accompanied by a sharp increase in the content of water condensate in the oil and an increase in the degree of condensation of crankcase gases. The feasibility of using a combined test mode is substantiated, which includes a “cold” stage of engine operation, shutdown with forced pumping of a coolant of elevated temperature and further operation in a “hot” mode. It is shown that such a regime provides intensification of corrosion processes and at the same time allows to obtain reproducible results in a relatively short time. Criteria for assessing the protective properties of motor oils are proposed based on the corrosion induction period, the number of parts with corrosion foci, the area and nature of corrosion damage to the control plate and elements of the gas distribution mechanism. A correlation between the amount of cylinder liner wear and the indicators of corrosion damage to control elements is established, which allows for the use of simplified express assessment without lengthy resource tests. As a result of optimizing the duration of the cycles, a rational three-hour test regime was determined, which provides a clear fixation of the beginning of the corrosion induction period and increases the sensitivity of the method to differences in the protective properties of different oils. The comparative tests conducted showed that the introduction of combined corrosion inhibitors significantly increases the anti-corrosion efficiency of motor oils, while the highest protective properties are demonstrated by synthetic working and conservation oils with inhibitors of complex action. The proposed method can be used for scientific research, development and comparative assessment of motor oils in terms of their protective properties.
Method for motor evaluation of the protective properties of internal combustion engine oils
Keywords: моторна олива; електрохімічна корозія; індукційний період корозії; конденсація картерних газів; захисні властивості; інгібітори корозії; гільза циліндра; газорозподільний механізм; випробувальний режим; motor oil; electrochemical corrosion; corrosion induction period; crankcase gas condensation; protective properties; corrosion inhibitors; cylinder liner; gas distribution mechanism; test mode